Profil Sosial Ekonomi Usaha Penganyam Daun Kelapa (Klangsah) di Kecamatan Abiansemal Kabupaten Badung - ASTAWA, I MADE PUJA; AMBARAWATI, I G. A. A.; DJELANTIK, A. A. A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
Socio-Economic Profile of Coconut Leaf Weaver (Klangsah) in Abiansemal District, Badung Regency One example of the use of coconut leaves in Bali is  klangsah .  Klangsah  are plaits made from old coconut leaves.  Klangsah  is used as a substitute for the roof in tents for traditional activities in Bali.The activity of weaving coconut leaves ( klangsah ) can provide job opportunities for the Balinese people. This research was conducted at the  klangsah  weaver business in Abiansemal District with the aim of knowing the socio-economic profile of the  klangsah  weavers and the income level of the  klangsah  weavers.The selection of the location was done intentionally and the selection of respondents was carried out by census, namely 18  klangsah  weavers in Abiansemal District.The data analysis technique used in this research is descriptive qualitative analysis and descriptive quantitative analysis.The results showed that the social profile of the  klangsah  weavers in Abiansemal District according to their identity, all of the  klangsah  weavers were productive age with low education with the majority of women as business owners. Meanwhile, the economic profile of the  klangsah  weavers in Abiansemal District when viewed from (1) the business network, where the origin of the supply of raw materials comes from collectors in Jembrana Regency and farmers around the business location, (2) business characteristics, where the capital owned comes from loan funds and personal funds assisted by family workers and casual workers having an average number of working hours of 7 hours per day, (3) income, in 2020 the total income of  klangsah  weavers is Rp29.881.003.